Woman Objectification and Its Social Abjection in Arthur Golden’s Memoirs of a Geisha (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2017)
Abstrak Memoirs of a Geisha karya Arthur Golden adalah salah satu novel biografi yang mengangkat kehidupan para geisha sebagai seorang penghibur. Dalam novel ini ditunjukkan bagaimana kehidupan para geisha yang rentan mengalami praktik objektifikasi terhadap perempuan. Di sisi lain, hidup sebagai geisha menimbulkan adanya kesenjangan antara gesha dengan masyarakat lainnya dalam bentuk abjeksi sosial. Untuk itulah tujuan penelitian ini adalah untuk memahami proses objektifikasi dan abjeksi sosial terhadap geisha dengan tiga rumusan masalah meliputi (1) untuk mengetahui alasan terjadinya objektifikasi perempuan terhadap geisha, (2) untuk menunjukkan abjeksi yang dialami Sayuri selama menjadi geisha (3) untuk mengetahui abjeksi masyarakat Gion terhadap geisha kelas rendah. Teori yang digunakan adalah teori objektifikasi oleh Fredrickson dan Robert, dan dilengkapi dengan teori milik Nussbaum, untuk menganalisis rumusan masalah pertama tentang objektifikasi. Sedangkan untuk rumusan masalah kedua dan ketiga akan menggunakan teori sosiologi literature tentang teori abjeksi sosial milik Imogen Tyler. Berdasarkan temuan yang ada, objektifikasi seksual yang terjadi pada geisha dipengaruhi oleh faktor lingkungan dan pekerjaan mereka. Dituntut untuk selalu tampil sedemikian rupa, membuat mereka mengalami objektifikasi diri sehingga objektifikasi seksual tidak dapat dihilangkan dari kehidupan Geisha. Dari lingkungan hidup mereka memunculkan adanya abjeksi sosial berupa penolakan dari masyarakat, baik itu kebencian spasial maupun moral. Kata Kunci: objektifikasi, objektifikasi perempuan, objektifikasi diri, abjeksi, abjeksi sosial. Abstract Arthur Golden’s Memoirs of a Geisha is a biography novel which raises the topic of geisha’s life as an entertainer or artist. This novel also shows how geisha’s life is closer to objectification. Living as a geisha creates the existence of a gap between geisha herself and the society around her in a form of social abjection. This study aims to understand the process of objectification and social abjection toward geisha in three main objectives; (1) to reveal the reason behind women objectification towards geisha, (2) to show the abjection that is experienced by Sayuri during her life as a geisha, and (3) to emphasize the abjection of lower class geisha by Gion society. Objectification theory by Fredrickson and Robert is being used, with additional material from Nussbaum’s theory in order to analyze the first research question. While for the second and third questions are using theory from the sociology of literature about social abjection by Imogen Tyler. Based on the findings, sexual objectification towards geisha is influenced by their surroundings such as their environment and their work. Demanded to be always presentable, their self-objectification is taking control their life so that sexual objectification cannot be denied from their life as a Geisha. Through this kind of surrounding, it leads into a social abjection in a form of a disgust feeling, whether it is spatial disgust or moral disgust. Keywords: objectification, women objectification, self-objectification, abjection, social abjection.